PREFERENSI SPASIAL DAN POSTURAL REMAJA DALAM RUANG GAMING NEIGHBORHOOD - Erza Rahma Hajaty; Hambali, Rizki; Handayani, Risky; Pintra, Azka; Waluyo, Dwi Oktyan (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
Teenagers' frequent use of social media, especially playing games, can cause a lack of time to interact directly with family or friends. Addiction to games can make teenagers become more closed and reduce the frequency of face-to-face communication so that it can make teenagers alienated from real life in their environment. So the balance of interaction between the digital world in games and the real world is very important. A gaming space that does not accommodate adolescents' activities to play games with friends will lead to a decrease in adolescents' desire to play games with friends face-to-face. Therefore, this study aims to determine the gaming spaces chosen by teenagers, the characteristics of the gaming space desired by teenage neighborhoods and the preferred gaming posture of teenagers. This research uses a qualitative method combined with the calculation of the percentage of category analysis results. The results showed that the space preferences for playing games chosen by teenagers are home, friends' houses, schools, cafes, and internet cafes. The characteristics of the space desired by teenage neighborhoods consist of free space to play games and be with friends, free space for expression and activity, comfortable and quiet space, facilitated space, concentration space, privacy space, inexpensive space. While the posture of playing games that teenagers like when playing games is sitting upright, sitting relaxed, relaxing freely. This research is useful to be the basis for designing gaming spaces and public interaction spaces that can accommodate and encourage the activity of playing games together with teenage neighborhood friends face-to-face, in increasing social interaction.